Enhanced cerebellar myelination with concomitant iron elevation and ultrastructural irregularities following prenatal exposure to ambient particulate matter in the mouse. (24th August 2018) - Klocke, Carolyn; Sherina, Valeriia; Graham, Uschi M.; Gunderson, Jakob; Allen, Joshua L.; Sobolewski, Marissa; Blum, Jason L.; Zelikoff, Judith T.; Cory-Slechta, Deborah A.
Abstract: Accumulating evidence indicates the developing central nervous system (CNS) is a target of air pollution toxicity. Epidemiological reports increasingly demonstrate that exposure to the particulate matter (PM) fraction of air pollution during neurodevelopment is associated with an increased risk of neurodevelopmental disorders (NDDs) such as autism spectrum disorder (ASD). These observations are supported by animal studies demonstrating prenatal exposure to concentrated ambient PM induces neuropathologies characteristic of ASD, including ventriculomegaly and aberrant corpus callosum (CC) myelination. Given the role of the CC and cerebellum in ASD etiology, this study tested whether prenatal exposure toc oncentrateda mbientp articles (CAPs) produced pathological features in offspring CC and cerebella consistent with ASD. Analysis of cerebellar myelin density revealed male-specific hypermyelination in CAPs-exposed offspring at postnatal days (PNDs) 11–15 without alteration of cerebellar area. Atomic absorption spectroscopy (AAS) revealed elevated iron (Fe) in the cerebellum of CAPs-exposed female offspring at PNDs 11–15, which connects with previously observed elevated Fe in the female CC. The presence of Fe inclusions, along with aluminum (Al) and silicon (Si) inclusions, were confirmed at nanoscale resolution in the CC along with ultrastructural myelin sheath damage. Furthermore, RNAseq and gene ontology (GO) enrichment analyses revealed cerebellar gene expression was significantly affected by sex and prenatal CAPs exposure with significant enrichment in inflammation and transmembrane transport processes that could underlie observed myelin and metal pathologies. Overall, this study highlights the ability of PM exposure to disrupt myelinogenesis and elucidates novel molecular targets of PM-induced developmental neurotoxicity.